An Exploration of Digital Music Nostalgia: Investigating the Reminiscence Bump through YouTube Streaming - Dera Raksaesa Regawa; Yudi Sukmayadi (Universitas Muhammadiyah Enrekang, 2025)
This study explores the phenomenon of the reminiscence bump within the context of digital music through the YouTube platform. The reminiscence bump refers to the tendency of individuals to recall events from adolescence to early adulthood more vividly, which in this study is activated through exposure to music from the 1990s and 2000s. Data were collected from 100 user comments on nostalgic music compilation videos and analyzed using thematic analysis techniques. The results indicate that music from adolescence and early adulthood evokes strong and emotional autobiographical memories. Dominant themes include school-time nostalgia, loss of loved ones, life reflection, and specific memories tied to particular songs. Music was found to be an effective medium for connecting the past to one's current identity. These findings support the theory that although media have transitioned to digital formats, the structure of autobiographical memory remains consistent. This study contributes to the fields of music psychology and memory research and highlights the potential application of nostalgic music in therapeutic and educational settings.